Linguistic manifestations in The Trimorphic Protennoia and The Thunder: Perfect Mind : analysed against the background of Platonic and Stoic dialectics - Halvgaard, Tilde Bak. (Nag Hammadi and Manichaean Studies, 2016)
Both the Thunder: Perfect Mind (NHC VI,2) and the Trimorphic Protennoia (NHC XIII,1) present their readers with goddesses who descend in such auditive terms as sound, voice, and word. In Linguistic Manifestations in the Trimorphic Protennoia and the Thunder: Perfect Mind, Tilde Bak Halvgaard argues that these presentations reflect a philosophical discussion about the nature of words and names, utterances and language, as well as the relationship between language and reality, inspired especially by Platonic and Stoic dialectics. Her analysis of these linguistic manifestations against the background of ancient philosophy of language offers many new insights into the structure of the two texts and the paradoxical sayings of the Thunder: Perfect Mind .